charm of the north - Елена Григорьева; Константин Лидин (Проект Байкал)
Our country occupies the largest part of the Arctic, and more than half of our territories are permafrost. The North is, first and foremost, the Russian North. From ancient wooden churches to settlements and small towns, either very young or historic – the whole region is now waking up to new life due to the grandiose plans for the development of the Arctic regions. Exotic toponyms – Tiksi, Neryungri, Severobaikalsk – are beginning to breathe new romance and pose new challenges to urban planners.